Barriers and Solutions in Implementing Competence-Based Curriculum: A Case Study of Chitungwiza District Primary Schools - Shinda, Mastina; Banda, Wilson (An Overview of Literature, Language and Education Research Vol. 5, 2024)
The shift of the Zimbabwean curriculum from a content-based to a competence-based curriculum has brought up some challenges in its implementation. Components within the new curriculum such as Continuous Assessment Learning Activities (CALA) and the introduction of new learning areas such as Science and Technology, and Information Communication Technology have caused disruptions in the implementation of the Competence Based Curriculum. The purpose of the study was to explore the challenges faced in the implementation of the competence-based curriculum in Chitungwiza district primary schools. The study used a qualitative case study of a primary school in Chitungwiza district in the Harare metropolitan province. Purposive sampling was utilised to select 23 research respondents, including 14 teachers, 6 parents, and 3 administrators. The study was guided by the constructivist perspective. The theory fosters the learners’ competencies such as problem-solving, critical thinking and creativity hence it matches the goals of this study. The case study design was exploited. The questionnaire, interview guide and focus group discussion were used to collect data. Qualitative data were analysed using the thematic data analysis methodology. The study exposed that the successful implementation of the competence-based curriculum (CBC) was hindered by a lack of both material and human resources. Overcrowded classes were a result of a lack of infrastructure such as classrooms in schools which resulted in hot seating in large classes in a single classroom. Low teacher morale was cited as a recurrent barrier to effective curriculum implementation. It was established that most teachers lacked the basal CBC implementation skills, competencies, and knowledge, as most of them were trained well before the introduction of the new curriculum. Overarching recommendations were that proper planning should be done before the implementation of any transformative curriculum programme. The demands of the CBC were difficult to fulfil without proper planning and the involvement of all key stakeholders. The school, community and the government all need to work together to ensure the successful implementation of the CBC. Henceforth, the central government and its partners should avail the requisite financial, material, infrastructural and human resources prior to the envisaged curriculum implementation. Teachers, on the one hand, should be positively incentivised as paramount CBC actors. Their seamless morale boost should never be overemphasised if desired curricula goals are to be achieved.